Who’s In and Who’s Out? War News from Mexico and the Framing of Evil - Alan Hirsch (Sillages Critiques)
In Richard Caton Woodville’s 1848 painting, War News from Mexico, eleven figures crowd in and around a portico. Eight white men occupy the same physical plane and respond to word of America’s victory in the Mexican War. Three other figures – black, female, or both – are outside the portico. That the blacks, who were most directly affected by the war, are ignored by the whites above them, implies a political statement. The painting’s geometry suggests that it is also a painting about painting. The rectangular portico evokes a canvas and, I will argue, the man seated to the left is Woodville. Just as the rectangular portico evokes a canvas, so too the newspaper, perfectly centered within the portico. We have, then, a canvas within a canvas within a canvas. The exclusion of the blacks from the celebration mirrors the fact that the newspaper itself was produced by and for whites. The artist, his right arm cocked in painterly position, takes in the scene that he will frame for us. The work reifies the notion of inside and outside: white men within the pillars of power and controlling discourse; blacks and women, overlooked in the margins and at their mercy; and the artist, occupying the distinct position of outsider within. Of course, our perspectives are ultimately framed by our eyes (often with the assist of framed eyeglasses), though artists influence our frames of reference. Woodville’s awareness of his power (and impotence, as he could hardly stop slavery) helps explain the painting’s most idiosyncratic feature: a peacock feather attached to the black man’s hat. In the myth of Argus, the hundred-eyed giant wins the favor of Juno by using his hyper-optic capacity for her benefit. To memorialize him, the goddess has his eyes preserved in a peacock’s tail. This allegorical evocation of the rewards of visual vigilance embodies War News’ meta-framing.